Tibiotalocalcaneal joint resection using a conical ultrasonic debridement probe - Trevor S. Page, BS; Evan W. Schneider, BA; Robert M. Joseph, DPM, PhD, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases, 2024)
Thermal necrosis and neurovascular injury both contribute to complications associated with saw and rotary burr joint resection techniques. Ultrasonic debridement is atraumatic and purportedly isolates necrotic tissue while sparing living tissues of thermal injury. This case demonstrates successful use of an ultrasonic debridement technique for cartilage resection when performing a tibiotalocalcaneal arthrodesis. A 50-year-old diabetic male with a Chopart amputation suffered from a chronic wound caused by weightbearing on his stump that was fixed in 40 degrees of plantarflexion contracture. The deformity was surgically corrected in a staged fashion with the first stage consisting of equinus deformity correction. The second stage consisted of stabilization of limb realignment by performing a tibiotalocalcaneal arthrodesis with intramedullary rod fixation. A conical shaped ultrasonic probe designed for debridement of tunneling soft tissue wounds was utilized to debride cartilage from the ankle and subtalar joints. Radiograph and CT imaging demonstrated stable arthrodesis with rectus alignment of the limb and intact internal fixation at 14 months postop. In conclusion, ultrasonic denudement of cartilage may be an alternative to saw and burr techniques of cartilage resection when performing an arthrodesis that reduces the risk of thermal necrosis, traumatic injury and joint distraction.